Multifunctional Reconfigurable Millimeter-Wave Array Antenna - Rawad W. Asfour; Salam K. Khamas; Edward A. Ball (IEEE Access)
This paper presents the design and implementation of an innovative 4-element multifunctional reconfigurability array antenna (MRAA) operating at 27.5 GHz, leveraging PIN diodes for enhanced functionality. By strategically controlling the alignment of PIN diodes, the antenna utilizes only two coplanar strip line biasing networks, streamlining its design and implementation. The proposed array demonstrates exceptional versatility by easily generating scanning beams at angles up to ±25° across three distinct polarizations: right-hand and left-hand circular polarizations and linear polarization. Furthermore, the system achieves a reconfigurable frequency interface between circular and linear polarizations, enhancing its adaptability to diverse communication scenarios. Through comprehensive analysis, the proposed MRAA exhibits commendable array gain, surpassing 10 dBic, and very good radiation efficiency exceeding 74%. This work marks the pioneering effort in designing a multifunctional reconfigurable array antenna for millimeter-wave (mmWave) applications. Additionally, the proposed array offers simplicity in design and outperforms existing counterparts operating at lower frequencies. A prototype has been fabricated, and measurement results demonstrate close agreement with simulation, validating the efficacy of the proposed design.